Bridges or buffers? Motives behind immigrants' religiosity - A comparative study of Europe and the United States - Teresa Garcia-Mu\~noz; Shoshana Neuman (Bar-Ilan University, Department of Economics, 2013)
This study reviews and evaluates the motives and incentives behind immigrants' religiosity, focusing on the two sides of the Atlantic - Europe and the United States. The contribution of the study is mainly empirical, trying to identify indicators for the type of incentive - whether immigrants' religiosity serves as a bridge or a buffer in the process of adaptation to the receiving country. The statistical analysis draws on data from several waves of the European Social Survey (ESS), the American General Social Survey (GSS), and the International Social Survey Program (ISSP). Estimation of extended mass participation equations and prayer equations leads to the following findings: (a) immigrants are indeed more religious than the populations in the receiving countries, both in Europe and in the United States; and (b) while in the United States the religiosity of immigrants serves as a bridge between the immigrants and the local population, in Europe it has mainly the function of a buffer and of a balm for the soul. There is an extensive literature on the bridge versus buffer (or bridge versus boundary) theories and their different implications in the United States and in Europe. However, to the best of our knowledge, our paper presents an innovative attempt to disentangle the two types of motives and to show that while the former is more relevant in the United States, the latter dominates in Europe.
Keywords: J11; J15; Z12; Z13; 330; immigration; religion; integration; Europe; The United States; bridge; buffer